New developments in international agricultural trade: A threat or a chance for LDCs and CEECs? - Monika Hartmann (Intereconomics, 1995)
The nineties have seen a number of developments which will have major consequences for international agricultural trade. Will the changed conditions in the world agricultural markets enable less developed countries (LDCs) and Central and Eastern European countries (CEECs) to exploit their comparative advantages better, or will the reforms further squeeze them out of the industrial countries' markets?
Keywords: 330; Agricultural Trade